Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Niat Bertahan Karyawan Sektor Kesehatan yang Dimediasi oleh Kepuasan Kerja: Tinjauan Literatur Sistematis - Wardani, Yusnita; Soetjipto , Budi Eko; Wardana, Ludi Wishnu (Universitas Negeri Surabaya, 2024)
Employee performance is a critical component of organizational success, influenced by various internal and external factors. This study employs a Systematic Literature Review (SLR) to explore recent findings on how workload and work environment influence the intention to stay among health sector employees in developing countries, with job satisfaction as a mediating variable. Using the PRISMA framework, 1,524 articles published between 2020 and 2025 were identified from Emerald, ScienceDirect, and PubMed, focusing on keywords such as workload, work environment, job satisfaction, and intention to stay. After applying inclusion and exclusion criteria, 23 articles were selected for in-depth analysis. The review reveals that workload significantly influences job satisfaction, particularly in relation to task distribution by management. A supportive work environment also enhances job satisfaction through psychosocial support mechanisms, which can impact patient outcomes. Furthermore, job satisfaction positively affects the intention to stay, emphasizing the role of organizational commitment. Both workload and work environment directly influence retention, where excessive workload and negative workplace conditions reduce employee persistence. Job satisfaction is found to mediate these relationships, highlighting the importance of aligning workload, workplace conditions, and fair compensation. This study provides valuable insights for healthcare institutions, particularly hospitals, to improve employee retention and service quality through better work design and supportive environments.